2021
DOI: 10.4028/www.scientific.net/ssp.317.119
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Magnetic Properties between Fe and Ni Doped ZnO Nanoparticles Synthesized by Microwave Assisted Synthesis Method

Abstract: The emergence of Dilute Magnetic Semiconductors (DMS) with a potentials for spintronic application have attracted much researches attention, special consideration has been given to ZnO semiconductor material due to its wide band gap of 3.37 eV, large exciting binding energy of 60 meV, moreover, its ferromagnetic behavior at room temperature when doped with transition metals. MxZn1-xO (M = Fe or Ni) nanoparticles were synthesized by microwave assisted synthesis method calcined at 600°C. The structural, morpholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Said et al used a microwave-assisted synthesis method, calcined at 600℃, and doped Fe or Ni into ZnO nanoparticles. Research has confirmed that ZnO doped with Fe atoms has high saturation magnetization, while ZnO doped with Ni has high coercivity [3]. Doping can regulate the impurity-related luminescent properties of ZnO nanorod materials, enabling them to exhibit excellent luminescent properties in both green and orange light bands.…”
Section: Introductionmentioning
confidence: 99%
“…Said et al used a microwave-assisted synthesis method, calcined at 600℃, and doped Fe or Ni into ZnO nanoparticles. Research has confirmed that ZnO doped with Fe atoms has high saturation magnetization, while ZnO doped with Ni has high coercivity [3]. Doping can regulate the impurity-related luminescent properties of ZnO nanorod materials, enabling them to exhibit excellent luminescent properties in both green and orange light bands.…”
Section: Introductionmentioning
confidence: 99%